KONTAMINASI BAKTERI KOLIFORM PADA AIR MINUM ISI ULANG DI DESA ILIE KECAMATAN ULEE KARENG KOTA BANDA ACEH (Contamination of Coliform in Refill Water in Ilie Village, Ulee Kareng, Banda Aceh) - M. Iqbal Pratama Sekedang; Zakiah Heryawati Manaf; Darmawi Darmawi; Faisal Jamin; Mahdi Abrar; Razali Razali (Universitas Syiah Kuala, 2016)
The purpose of this study was to find out whether the refill water (AMIU) was contaminated with coliform or not. The methods used were presumptive, confirmed, and completed test. Sample of this study was refill water (AMIU) from five refill water shops located in Ilie village, sub-district of Ulee Kareng, Banda Aceh. The sample was taken 3 times with interval period of one week. Sample was culture in lactose broth and incubated at 37° C for 48 hours. If it did not form gas in Durham tube, presumptive test result was considered negative and the samples were not proceed to the other test. The data was presented using descriptive analysis. It could be concluded that AMIU from 5 shops in Ilie Ulee Kareng, Banda Aceh is negatively contaminated with coliform bacteria.